The threat of animated films to national disintegration in the dimension of character formation of alpha generation: A Study in Mataram City - Bagdawansyah Alqadri; Rispawati Rispawati; M. Samsul Hadi; Maria Grace Putri Edi; Nurlatifa Nurlatifa; Lianda Dewi Sartika; Rizky Wahyuni (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This research departs from the growing urgency of the high consumption of foreign animated films among Generation Alpha in Mataram City, which may weaken national identity and character. The selection of Mataram City as the research site is grounded in its role as a heterogeneous social laboratory; it serves as a strategic case study to examine the tension between deeply rooted local traditions and the pervasive influence of global digital media. This study aims to explore how foreign animation shapes children's perceptions and to gain a profound understanding of potential shifts in national integration values in their everyday lived experiences. The primary subjects are Generation Alpha children (aged 4–12 years), purposively selected to provide deep insights, with parents and teachers serving as secondary informants for data triangulation. The specific object of the study is the phenomenon of identity construction and the potential erosion of national character resulting from prolonged media exposure. Using a qualitative phenomenological approach, data were obtained through observation, in-depth interviews, and documentation. The findings reveal that intensive daily exposure to foreign animation leads to the internalisation of global values, manifested in the imitation of foreign accents and a shift toward individualistic behaviour, thereby challenging traditional social cohesion. Conversely, local animations such as Nussa & Rara are found to reinforce religiosity, cooperation, and manners. These results underline that without media literacy and support for local content, foreign animation poses a challenge to national identity. Systematic synergy between schools, families, and the government can transform animation into a strategic tool for strengthening character education and national integration.